Sodium sulfite research and microbiological analysis of ground beef and fresh sausage (Research, Society and Development, 2021)
In general, the meat contains nutrients of high biological value and susceptible to contamination by enteropathogens. One way of minimizing/eliminating this contamination is the use of food additives, in the case of meat, usually sodium sulphite. This technological resource is used to inhibit the growth of pathogenic bacteria such as Salmonella spp. and thermotolerant coliforms, mandatory parameters foreseen in sanitary legislation. Therefore, the objective of this article was to evaluate the presence of sodium sulfite and detection of Salmonella spp., total and thermotolerant coliforms in 23 samples of ground beef and 7 of fresh pork sausage, marketed in open markets and public markets of Grande Recife - PE. In a total of 30 samples analyzed, it was not detected in any presence of sodium sulphite. In the microbiological assays, also it was not detected the presence of Salmonella spp. and thermotolerant coliforms. The Total Coliforms was found in 20 meat samples (87%), at the maximum concentration of 35 MPN/g-1 and in all sausages (100%) at the concentration of 35 to 36 MPN/g-1. Although the Total Coliforms is not considered pathogenic, the presence of this indicates unsatisfactory sanitary conditions in the production, which may constitute biological risk for vulnerable groups.